(untitled) (Journal of Pharma Insights and Research, 2024)
Pharmacogenomics, situated at the nexus of genomics and pharmacology, represents a paradigm shift in healthcare by advocating personalized medicine over conventional one-size-fits-all drug therapy. This review article covers the origins, core principles, and current developments in pharmacogenomics, tracing its inception to the completion of the Human Genome Project. By investigating how genetic variations influence individual responses to medications, pharmacogenomics addresses the persistent challenge of inter-individual variability in drug efficacy, toxicity, and adverse reactions. Emphasis is placed on the pivotal role of key drug-metabolizing enzymes, notably the cytochrome P450 family, in shaping drug responses. The review provides historical milestones and foundational principles, offering a comprehensive understanding of the intricate interplay between genetics and drug response. As we decode the genetic blueprint, the potential to tailor drug regimens based on individual genetic profiles becomes increasingly feasible. The evolving landscape of pharmacogenomics holds promise in optimizing drug outcomes and minimizing adverse effects, ushering in a new era of patient-centered healthcare